ANALISIS KOMUNIKASI GURU DALAM MEMBINA KEMANDIRIAN HIDUP BERASRAMA SISWA KELAS 5 MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Nurul Karimah, Muthia; Iswandi, Irvan; Utami, Dewi (Sindoro: Cendikia Pendidikan, 2024)
Fostering student independence, especially in boarding life away from parents, is very important. A teacher must be able to communicate well in the process of fostering and supervising this independence. Teachers have an active role in fostering student independence, so good communication between teachers and students is absolutely necessary. Thus, students' independence can be well formed through the active role and effective communication of the teacher. This thesis examines how the independence of 5th grade students of MI Ma'had Al-Zaytun in dormitory life and teacher communication in fostering the independence of life. This research method uses descriptive research with a qualitative approach. Data collection was conducted through observation and in-depth interviews with students and 5th grade teachers of MI Ma'had Al-Zaytun. The research subjects consisted of 35 students and 4 5th grade teachers of MI Ma'had Al-Zaytun. The results showed that the life independence of 5th grade students of Madrasah Ibtidaiyah Ma'had Al-Zaytun was influenced by internal and external factors. Internal factors include intrinsic motivation, level of self-confidence, and ability to manage time. External factors include the school environment, life skills guidance from teachers, as well as the influence of independent peers. In addition, this study explores the importance of teacher communication in fostering students' life independence. Grade 5 teachers of Madrasah Ibtidaiyah Ma'had Al-Zaytun use interpersonal and group forms of communication. And a combination of verbal and nonverbal communication is also used to convey information clearly, thus creating a dynamic learning environment, and supporting students' holistic development. These communication strategies help students to increase their independence and develop time management skills that are essential in boarding school life. Keywords: teacher communication, student independence, boarding school